Trends in Digital Transformation for Multicultural E-Government Communication: A Bibliometric Analysis Using Citespace - Hadmar, Ahmad Muhardin; Nurmandi, Achmad; Sadat, Anwar; Loilatu, Mohamad Jafar; Hassan Ibrahim, Adil (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
Digital transformation in public services is essential for enhancing government performance and modernizing systems. In the realm of multicultural communication, it's crucial that technology is both technically effective and culturally inclusive. This research analyzes trends in digital government transformation from 2018 to 2022, revealing 340 indexed research articles in the Scopus database. Using qualitative research and bibliometric analysis with CiteSpace software, the study examines publications based on the number of articles, contributing countries, fields of study, authors, affiliated institutions, and citation counts. The findings indicate a rising trend in publications, with computer science as a core discipline. Digital organizational resilience emerges as a dominant topic, emphasizing the need for governments to adapt to technological changes effectively. The University of the Aegean is noted as a leading institution, while Draheim has the highest contribution level, and Russia is identified as the most prolific contributing country. The implications suggest that for successful digital transformation, governments must prioritize inclusivity and cultural sensitivity in their technology strategies. This research contributes to understanding how multicultural communication can enhance digital initiatives and emphasizes the importance of considering all societal segments in policy development. Ultimately, the findings lay a foundation for developing a more inclusive government through sustainable technology and recognition of cultural diversity, enabling better engagement and service delivery to diverse communities.Keywords: Bibliometric Analysis, CiteSpace, Digital Transformation, E-Government, Multicultural Communication. AbstrakTransformasi digital dalam pelayanan publik merupakan langkah untuk meningkatkan kinerja pemerintahan dan modernisasi sistem pemerintahan. Dalam konteks komunikasi multikultural, penting untuk memastikan bahwa teknologi tidak hanya efektif secara teknis namun juga inklusif secara budaya. Penelitian ini menganalisis tren transformasi pemerintahan digital dalam lima tahun terakhir, yaitu pada tahun 2018 hingga 2022. Temuannya, terdapat 340 artikel penelitian tentang transformasi pemerintahan digital yang terindeks di database Scopus. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi literatur. Penelitian ini menerapkan analisis bibliometrik menggunakan software CiteSpace. Selanjutnya makalah disajikan berdasarkan jumlah publikasi, negara kontributor, bidang studi, penulis, institusi afiliasi, isu terkait, dan sitasi tinggi. Penelitian ini menunjukkan tren publikasi yang meningkat, dengan ilmu komputer menjadi disiplin inti dalam penelitian ini. Melalui analisis beberapa sumber, ketahanan organisasi digital menjadi trending topik yang dominan. Selain itu, Universitas Aegean adalah institusi terkemuka. Draheim merupakan penulis dengan tingkat kontribusi tertinggi, namun Rusia menjadi negara yang memberikan kontribusi paling besar. Pada akhirnya, hasil penelitian tersebut menjadi preferensi untuk mengembangkan pemerintahan yang lebih inklusif dengan menerapkan teknologi berkelanjutan dan mempertimbangkan keberagaman budaya.Kata Kunci: Analisis Bibliometrik, CiteSpace, Transformasi Digital, E-Government, Komunikasi Multikultural.